2014
DOI: 10.1037/a0036353
|View full text |Cite
|
Sign up to set email alerts
|

Toward a greater understanding of the emotional dynamics of the mortality salience manipulation: Revisiting the “affect-free” claim of terror management research.

Abstract: The experimental manipulation of mortality salience (MS) represents one of the most widely used methodological procedures in social psychology, having been employed by terror management researchers in hundreds of studies over the last 20 years. One of the more provocative conclusions regarding this task is that it does not produce any reliable changes in self-reported affect, a view that we refer to as the affect-free claim. After reviewing 336 published studies that used the standard version of the MS task, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 129 publications
12
113
3
3
Order By: Relevance
“…Extant research suggests that while MS manipulations such as that used here do not generally increase negative affect (Burke et al, 2010), it can produce effects on affect (both positive and negative) that are typically relatively small (Arndt, Allen, & Greenberg, 2001;Burke et al, 2010). Further, recent research suggests that the affective consequences of MS may indeed lie more with fear than generalized negative affect, though these small increases in fear do not mediate effects on outcomes related to worldview defense (Lambert et al, 2014), and have not been found in a number of other studies. Because this MS effect on fear did not replicate in Studies 2 and 3, we do not discuss it further.…”
Section: Discussionmentioning
confidence: 94%
“…Extant research suggests that while MS manipulations such as that used here do not generally increase negative affect (Burke et al, 2010), it can produce effects on affect (both positive and negative) that are typically relatively small (Arndt, Allen, & Greenberg, 2001;Burke et al, 2010). Further, recent research suggests that the affective consequences of MS may indeed lie more with fear than generalized negative affect, though these small increases in fear do not mediate effects on outcomes related to worldview defense (Lambert et al, 2014), and have not been found in a number of other studies. Because this MS effect on fear did not replicate in Studies 2 and 3, we do not discuss it further.…”
Section: Discussionmentioning
confidence: 94%
“…Most studies looking at this relationship have focused on the effects of MS on self-reported negative affect. The earliest work on this topic found no effects of MS on negative affect (see Arndt et al (2001);Lambert et al 2014 for reviews). However, more recent work has revealed movement on affective measures for some individuals, under certain conditions, or when more sensitive measures of negative affect have been utilized.…”
Section: Thoughts Of Death and Aversive Emotionmentioning
confidence: 98%
“…Similarly, Arndt et al (2001) found increases in facial EMG following a subliminal death prime, though this increase did not mediate the effect of priming death on worldview defense. Recently, Lambert et al (2014) found that MS increased self-reported anxiety, and especially fear, when utilizing more targeted measures of these affective states. In one study, this increase in fear was found to mediate the influence of MS on state self-esteem, but in another study fear did not mediate the effect of MS on worldview defense.…”
Section: Thoughts Of Death and Aversive Emotionmentioning
confidence: 99%
“…With the exception of theories of uncertainty, the role of affect in epistemic threat/defence models has been limited and vague (Lambert et al, 2014). Many models propose that some form of aversive arousal precedes the compensatory responses that discrepancy based threats can trigger (Festinger, 1957;Proulx & Inzlicht, 2012).…”
Section: Implications and Contributionsmentioning
confidence: 99%